AB0020 Expression levels of signaling lymphocyte activation molecule family 6 (SLAMF6) on circulating follicular helper T cells are associated with disease activity in systemic lupus erythematosus. (15th June 2017) - Kang, SE; Lee, SJ; Go, DJ; Kwon, HM; Ahn, EY; Park, JK; Lee, EY; Lee, EB; Song, YW
Abstract : Background: T follicular helper cells (Tfh) are necessary for B-cell maturation and differentiation in the germinal centers (GC). The signaling lymphocyte activation molecule family (SLAMF) receptors on the cell surface mediate T cell:B cell interaction for formation and maintenance of GC. But it remains to be elucidated whether SLAMF is expressed in circulating T follicular helper cells (cTfh). Objectives: The aim of this study was to investigate the levels of SLAMF3 and SLAMF6 on cTfh and to analyze their association with disease activity in systemic lupus erythematosus (SLE) patients. Methods: Blood samples were collected from 50 SLE patients, 24 Sjogren's syndrome (SS) patients and 25 age- and sex-matched healthy controls (HCs). In this study, CXCR5, programmed cell death protein 1 (PD-1), and CD4 were used as markers to define cTfh in peripheral blood mononuclear cells (PBMCs). The expression levels of SLMAF3 and SLMAF6 on cTfh were compared to that of circulating B cell subsets by flow cytometry. Clinical features including disease activity and laboratory tests were analyzed according to expression of SLAMF3 and SLAMF6. Results: Surface expression of SLAMF6 on CD4 T cells was significantly increased in SLE patients compared to SS patients (mean fluorescence intensity [MFI], mean ± SD: 1291±319 vs 1098±147, p=0.015) and HCs (1291±319 vs 1094±243, p=0.011). But there was no difference in expression of SLAMF3 on CD4 T cells between SLE patients and SS patients or HCs. SLAMF6 expressions on cTfh cells, identified as CD4 + CXCR5 + PD-1 +, were significantly increased in SLE patients than in SS patients (1500±270 vs 1296±140, p=0.001) and HCs (1500±270 vs 1295±161, p=0.001). SLAMF6 expressions on cTfh cells had correlation with systemic lupus erythematosus disease activity index (SLEDAI) (Spearman's rho=0.477, p=0.001), proteinuria (rho=0.321, p=0.030) and double strand DNA (rho=0.340, p=0.026) in SLE patients. Moreover, expression levels of SLAMF6 on cTfh cells were correlated with those of several B cell subsets including total B cells (CD19 + ), naïve B cells (CD19 + CD27 - IgD + ) and class-switched memory B cells (CD19 + CD27 + IgD - ). But SLAMF6 expressions of B cell subsets were not correlated with disease activity. Conclusions: Surface expression of SLAMF6 was increased in cTfh cells in patients of SLE and had correlation with disease activity. References: T cells indicate Tfh cell activity and promote antibody responses upon antigen reexposure. Immunity. 2013;17;39(4):770–81. Choi JY, His-enHo J, Pasoto SG, et al. Circulating follicular helper-like T cells in systemic lupus erythematosus: association with disease activity. Arthritis Rheumatol. 2015;67(4):988–99. Zhang X, Lindwall E, Gauthier C, et al. Circulating CXCR5+CD4+helper T cells in systemic lupus erythematosus patients share phenotypic properties with germinal center follicular helper T cells and promote antibody production. Lupus. 2015;24(9):909–17. Disclosure of Interest: None declared